Procesos atencionales en estudiantes con trastornos específicos del aprendizaje en Educación Básica Elemental - Álvarez Mazón, Zaida Margarita (2021)
The research work presented is entitled Attentional processes in students with specific developmental learning disorders in Basic Elementary. The problem investigated is related to How to contribute to the capacitation of teachers for the improvement of attention processes in students with specific learning disorders of the fourth year of Basic General Education. It was developed in the Playas de Villamil District of the Guayas province, in two educational institutions of Basic General Education where 12 students with specific learning disorders and three teachers who attend them were selected. The approach used was mixed and the scope of the research was descriptive. ………….